2005
DOI: 10.1007/s10620-005-2770-y
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Reduces Rectal Distension-Induced Blood Pressure Changes in Conscious Dogs

Abstract: It has been shown that acupuncture relieves symptoms of abdominal pain and bloating in patients with irritable bowel syndrome (IBS). However, the mechanism of beneficial effects of acupuncture still remains unproven. The aim of the present study was to investigate the mechanisms of the antinociceptive effects of acupuncture in conscious dogs. We evaluated the increase in mean arterial blood pressure (MAP) caused by rectal distension as an index of visceral pain. Electroacupuncture (EA; 10 Hz) at ST-36 (lower l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…On the other hand, the analgesic effect of AP has been reported to be mediated by an endogenous opioid pathway (19,48). A previous canine study reported that the painful sensation induced by rectal distension was attenuated by EA at ST-36, and the effect was abolished by pretreatment with naloxone, but not naloxone methiodide, suggesting a central opioid pathway (31). The relationship between the vagal pathway and opioid pathway is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the analgesic effect of AP has been reported to be mediated by an endogenous opioid pathway (19,48). A previous canine study reported that the painful sensation induced by rectal distension was attenuated by EA at ST-36, and the effect was abolished by pretreatment with naloxone, but not naloxone methiodide, suggesting a central opioid pathway (31). The relationship between the vagal pathway and opioid pathway is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies were also performed on the RD-induced inhibition in small intestinal motor activity in humans and animals (22,35). More recently, Iwa et al (19) studied the effects of EA on the nociceptive pathway using the RD model. However, little information is available on the effects and mechanisms of RD on gastric contractions.…”
Section: Effects and Mechanisms Of Rd On Gastrointestinal Motilitymentioning
confidence: 99%
“…Also, the mechanism of how RD impairs gastric motility is unclear. It may be mediated via the neural reflex, and either the nociceptive or nonnociceptive afferent pathway is involved, which is correlated with distension volumes and visceral sensation (19). More recent studies showed that sympathovagal balance was altered in IBS patients (23,41,45), but it is not clear whether these activities are altered with RD.…”
mentioning
confidence: 99%
“…These findings suggest that EA at ST-36 may reduce visceral pain via a central opioid pathway. 69 It has been well demonstrated that the analgesic effect of acupuncture is mediated by an endogenous opioid pathway. 32,33 Opioid signaling plays a pervasive role in the medullospinal network that controls sympathetic tone and arterial pressure.…”
Section: Effects Of Acupuncture On Visceral Painmentioning
confidence: 99%